A Germany-wide survey of caregiving professionals on climate change and mental health of children and adolescents - factors influencing their relevance rating of extreme weather event associated mental health impairments - Annika Hieronimi; Fiona O'Reilly; Michael Schneider; Inga Wermuth; Gerd Schulte-Körne; Lena Lagally; Stephan Bose-O'Reilly; Erik Danay (BMC, 2024)
Abstract Introduction Climate change presents a significant risk for the mental and physical health of young people. In order to identify and properly care for potential mental health impairments from extreme weather events, the relevance of these impairments must be assessed as high by the professional groups providing care for children and adolescents. This raises the question of which factors influence the individual relevance assessment of caretaking professionals? Methods Data was collected creating and conducting a Germany-wide online questionnaire via LimeSurvey. The questionnaire was addressed to professionals providing care for children and adolescents, in this case medical and therapeutic personnel as well as school and pedagogical personnel. Professional associations, chief physicians and school principals were contacted as multipliers and asked to forward the questionnaire to their members and staff. The data was analyzed using the R statistical software, and multiple linear regressions were performed to test the hypotheses. Results Overall, 648 questionnaires were taken into analysis. Approximately 70% of the participants considered climate change-induced impacts on the mental health of children and adolescents due to extreme weather events as relevant. Experiencing heat, storm, heavy precipitation, flood/flooding, and/or avalanches/mudflows made a modest yet significant contribution to explaining higher relevance assessments. In contrast, there was no evidence to suggest that an urban working environment increases the relevance assessment. Conclusion The described influence of experiencing extreme weather events should not be regarded as the sole factor leading to higher relevance ratings. A more comprehensive understanding of the factors influencing relevance assessments is necessary to address key aspects of risk communication and increase risk awareness.